IN GENERAL EDUCATION SCHOOLS, PRACTICAL AND LABORATORY EXERCISES IN 8TH GRADE PHYSICS ARE CARRIED OUT USING THE "CROCODILE PHYSICS" PROGRAM - S. Davletniyazov; G. Seytmuratova (Journals Park Publishing, 2023)
This article discusses the opportunities for practical and laboratory activities in teaching 7th grade physics using the Crocodile Physics program.
Keywords: Crocodile Physics program, virtual laboratory work, innovative technology, measuring electric circuit current and resistance in various parts of it during laboratory work.